2012
DOI: 10.1002/eqe.2161
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear behavior of high‐damping rubber bearings under horizontal bidirectional loading: full‐scale tests and analytical modeling

Abstract: SUMMARY Horizontal bidirectional loading tests are conducted for real‐sized high‐damping rubber (HDR) bearings with diameters of 700 mm (HDR700) and 1300 mm (HDR1300). The hysteresis loops of these bearings under bidirectional horizontal loadings are compared with those under unidirectional loadings. The results show that the bearing force measurement in the primary direction of loading increases when there is displacement in the orthogonal direction. Unusually, the maximum restoring force in the orthogonal di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(31 citation statements)
references
References 10 publications
1
30
0
Order By: Relevance
“…On the basis of the test results the model assumes that the restoring force on the rubber bearing is composed of a force directed to the origin of the bearing (non-linear elastic component of the force), and another force approximately opposite to the direction of the movement of the bearing (elastoplastic component of the force). Validation calculations have shown that the analytical model is able to accurately simulate the test results for both bidirectional and unidirectional loading [39]. For a detailed description and implementation of the analytical model that describe the nonlinear behavior of the isolators the reader is referred to [40,39].…”
Section: Implementation Aspectsmentioning
confidence: 98%
See 1 more Smart Citation
“…On the basis of the test results the model assumes that the restoring force on the rubber bearing is composed of a force directed to the origin of the bearing (non-linear elastic component of the force), and another force approximately opposite to the direction of the movement of the bearing (elastoplastic component of the force). Validation calculations have shown that the analytical model is able to accurately simulate the test results for both bidirectional and unidirectional loading [39]. For a detailed description and implementation of the analytical model that describe the nonlinear behavior of the isolators the reader is referred to [40,39].…”
Section: Implementation Aspectsmentioning
confidence: 98%
“…Validation calculations have shown that the analytical model is able to accurately simulate the test results for both bidirectional and unidirectional loading [39]. For a detailed description and implementation of the analytical model that describe the nonlinear behavior of the isolators the reader is referred to [40,39]. A typical displacementrestoring force curve of the rubber bearing is illustrated in Fig.…”
Section: Implementation Aspectsmentioning
confidence: 98%
“…As the test setup shown in Figure , it is noted that the upper and lower flange plates of the tested bearings were not twisted during the tests. Taking clockwise positive, the torsional (or twisting) moment at time t exerted on the flange plates because of nonproportional plane loading M t ( t ), as shown in Figure , can be calculated by Mt()t=()Fx()tUy()tFy()tUx()t/2 where F x ( t ) and F y ( t ) are the shear force components at time t measured in X and Y directions, respectively.…”
Section: Experimental Studymentioning
confidence: 99%
“…This behavior is often reported to be associated with high-damping rubber [31][32][33] and high-damping rubber bearings/isolators [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]. A number of mathematical models, including rheological models (for rubber material) [38] and constitutive/mechanical models (for rubber devices) [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48], have been proposed to characterize the strain stiffening behavior (in some literatures, it is called strain hardening [33,[36][37]). One of the common techniques in modeling the strain stiffening behavior is to introduce nonlinear power function spring or element.…”
Section: Rate-dependent Mechanical Models For Base Isolators 31 Stamentioning
confidence: 99%